PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Ratih Rachmadienti (2021)
This study aims to analyze the effect of institutional ownership, the competence of the board of commissioners, and audit committee on tax avoidance with profitability, leverage, and firma size as a controlling variable. The object of this research is mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, with a total sample of 38 companies. This research uses quantitative methods using panel data. The data analysis technique used is the classical assumption test, panel data estimation selection test, multiple linear regression test, and hypothesis testing using a significance of 5%. The results of this study indicate that the competence of the board of commissioners has an effect on tax avoidance, while institutional ownership and the audit committee have no effect on tax avoidance. This is because institutional shareholders cannot influence the policies made by management. In addition, the number of audit committee members according to the standards cannot ensure that the supervision carried out on managers is effective.